2023
DOI: 10.7759/cureus.35381
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Effectiveness of Low-Level Laser in Reducing Root Resorption of the Upper Incisors During Intrusion Movement Using Mini-Implants in Adult Patients With Deep Overbite: A Randomized Controlled Clinical Trial

Abstract: Background: Deep bite is a common characteristic of malocclusion, and many methods are used to treat it, including mini-implants used for the intrusion of the upper incisors. Orthodontically induced inflammatory root resorption (OIIRR) is an inevitable and unexpected side effect of orthodontic therapy. However, resorption of the root could be affected by the type of tooth movement, such as intrusion. Several studies have indicated the effectiveness of low-level laser therapy (LLLT) in accelerating orthodontic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
0
0
0
Order By: Relevance
“…Despite the benefits of 3D printing, milling stands out for its superior surface quality and material properties [26]. However, existing literature lacks comprehensive evaluations of the impact of different temporary crown fabrication techniques on periodontal health and patient experiences [27]. Most studies focus on isolated aspects of temporary crown construction, leaving a critical gap in evidence-based guidelines for optimal fabrication practices [28].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the benefits of 3D printing, milling stands out for its superior surface quality and material properties [26]. However, existing literature lacks comprehensive evaluations of the impact of different temporary crown fabrication techniques on periodontal health and patient experiences [27]. Most studies focus on isolated aspects of temporary crown construction, leaving a critical gap in evidence-based guidelines for optimal fabrication practices [28].…”
Section: Discussionmentioning
confidence: 99%
“…Studies performed with high-reliability micro-CT have not shown a great difference between the groups with and without LLLT [53]. Mini-implants were used in research on intrusive movement, and LLLT verified that the groups treated with LLLT reduced both volumetric and linear root resorption by 10 to 12% [60].…”
Section: Lllt and Root Resorptionmentioning
confidence: 97%